2021
DOI: 10.1080/17441692.2021.1965179
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported fertility impairments and help-seeking strategies among young women in Malawi

Abstract: This paper analyses wave 4 the Tsogolo la Thanzi survey of n = 1349 Malawian women aged 16-26 to explore the prevalence and predictors of self-reported fertility impairments (difficulties conceiving and/or difficulties carrying a pregnancy to term) and help-seeking strategies. Using descriptive statistics, logistic regression models, and graphic displays, the correlates of self-reporting an impairment and patterns of help-seeking strategies are examined. Nearly 13% (n = 117) of those who had ever tried to conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 51 publications
0
5
0
Order By: Relevance
“…The no toilet facility higher odds of fertility status when compared to the pit latrine toilet facility. The nding was supported by a similar study conducted in Malawi and India [34,35]. This could explain by inadequate water and toilet facilities during fertility status and childbirth are likely to lead to poor household and offspring outcomes [36].…”
Section: Discussionmentioning
confidence: 71%
“…The no toilet facility higher odds of fertility status when compared to the pit latrine toilet facility. The nding was supported by a similar study conducted in Malawi and India [34,35]. This could explain by inadequate water and toilet facilities during fertility status and childbirth are likely to lead to poor household and offspring outcomes [36].…”
Section: Discussionmentioning
confidence: 71%
“…To limit recall and social desirability bias, cases and controls, as well as the subjects’ mothers, were given a document to prepare for the telephone interview regarding their professional and residential history and were invited to bring their health records to the interview. Yet, we cannot exclude that social desirability bias may apply to responses to items such as fertility, medical history, smoking, alcohol consumption, and substance use, which constitutes a limitation in the present study ( 79–82 ). Pre- and perinatal factors of participants and the socio-economic status of mothers at birth were similar between the groups of subjects with interviewed and non-interviewed mothers ( 48 ).…”
Section: Discussionmentioning
confidence: 92%
“…The results of this study, which was conducted to determine the difficulties experienced by infertile Turkish women reported taking steps towards adoption [23,25]. Altıntop and Kesgin (2018) reported that the number of couples who want to adopt and become a foster family is low [16].…”
Section: Discussionmentioning
confidence: 99%
“…In this study, it was determined that 28.2% of the couples thought of using traditional treatment options, 3.1% thought of benefiting from donor germ cells and 20.7% thought of adoption (Table 3). Couples with infertility problems have a number of options, such as accepting childlessness, becoming a foster parent, adopting and using traditional and complementaryalternative methods [23]. In the literature, it has been revealed that the majority of couples do not consider an alternative method other than medical treatment, and 56% of them consider seeking medical help [16,17].…”
Section: Discussionmentioning
confidence: 99%